Palatability of wilted and dried multipurpose tree species fed to sheep and goats - Kaitho, R.J.; Umunna, N.N.; Nsahlai, I.V.; Tamminga, S.; Bruchem, J. van; Hanson, Jean (Elsevier, 1997)
Palatability indices of dry and wilted 18 multipurpose tree species (MPTs) were determined using 12 wethers and 12 bucks (mean (+ or -) SD liveweight 17.5 (+ or -) 1.24 kg and 20.5 (+ or -) 1.46 kg, respectively), blocked into two groups on liveweight and age, housed in a roofed and half-walled shed with individual feeding pens. The 19 MPTs were randomly grouped into sets of six by form (dried and wilted), such that each animal received three samples of each form. Each animal received 0.5 kg teff straw (Eragrostis tef) in addition to 0.4 kg and 0.2 kg of the wilted and dry forms of the appropriate MPTs, respectively, daily at 08:00 h over a 12-day experimental period. Dry matter intake of MPTs on day 1 (A1), average intakes on days 2-4 (A2), days 5-8 (A3), days 9-12 (A4) and days 2-12 (A5) were compared. A significant (P<0.0001) decrease in intake, with correlation coefficients of r=0.92 (A1 and A2), r=0.88 (A1 and A5), and r=0.85 (A1 and A3) in sheep, was observed. A similar trend was observed for palatability indices R1, R2, R3 and R4 and R5 (r=0.94). R1 was poorly correlated with R5 (r=0.61). The same trend was found in goats. Linear regressions of A5 and A3. The results of analysis of variance for palatability index R5 showed that the palatability index significantly (P<0.001) depended on previous clustering and animal species. The cluster means for R5 were 1.34, 1.02, 0.68 and 0.54 for clusters 1, 2, 3 and 4, respectively. However, the palatability indices for goats were more than double those for sheep (1.33 vs. 0.48). There were no significant interaction effects for cluster, form and animal species. In this study the form of feed (wilted or dry) did not affect the palatability index. Acacia persiciflora, Leucaena leucocephala and Chamaecytisus palmensis were ranked high by both sheep and goats.